INDIVIDUALISM IN ALL THE BRIGHT PLACES BY JENNIFER NIVEN - Tiara Arti Issar Nur Cahya; Abu Fanani; Amiq Amiq (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2022)
This article analyzes the individualism of the supporting characters towards the main character, Theodore Finch. Using descriptive and dramatic approach as the method and individualism as well as new criticism as theories, the researcher finds that the main character, Theodore Finch becomes the victim of the individualism of his teacher as well as his classmates. How the supporting characters are characterized in the analysis and how the main character is described becomes clear that individualism attached to the society Finch lives.